2018
DOI: 10.3390/w10040498
|View full text |Cite
|
Sign up to set email alerts
|

Indicator Values of Emergent Vegetation in Overgrowing Lakes in Relation to Water and Sediment Chemistry

Abstract: Lake overgrowth is one of the mechanisms affecting the gradual disappearance of lakes in the temperate zone caused by excessive eutrophication of waters. The aim of this study was to assess the possibility of using helophytes as bioindicators of lake overgrowth based on long-term changes based on the cartographic maps studies and field analyses of plant form growth cover (2012)(2013)(2014). Additionally, water and sediment chemistry in overgrowing lakes were investigated. The study comprised a total of 33 eut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…An analysis of lake eutrophication and shallowing was performed for 20 lakes located in the central-west part of Poland. The water bodies selected for the study have an area of less than 100 ha (Table S1; [18]) and had bathymetric plans prepared for them in the 1950s and 1960s. The reservoirs studied exhibited high biological productivity, with a Carlson's Trophic State Index [19] equal to 46-87, which corresponds to the eutrophic and hypereutrophic states.…”
Section: Methodsmentioning
confidence: 99%
“…An analysis of lake eutrophication and shallowing was performed for 20 lakes located in the central-west part of Poland. The water bodies selected for the study have an area of less than 100 ha (Table S1; [18]) and had bathymetric plans prepared for them in the 1950s and 1960s. The reservoirs studied exhibited high biological productivity, with a Carlson's Trophic State Index [19] equal to 46-87, which corresponds to the eutrophic and hypereutrophic states.…”
Section: Methodsmentioning
confidence: 99%
“…Map analysis of the range of rushes showed that the width of the zone depended on the water level, and the vegetation growth was determined by the water depth. The rush vegetation occurred at depths between 1.5 and 2.0 m [13,44], with the dominant species of reeds (Phragmites australis), narrowleaf cattail (Typha angustifolia), and spotted lakes (Scirpus lacustris). In areas with a rapidly falling slope, the occurrence of reeds was recorded even in zones with depths exceeding 2.5 m. Reed can grow in a relatively large amplitude of lake depth, but its optimal growth is observed in the range of 0 to 1.6 m [39,41], with roots reaching a maximum depth of 1.7 m [44].…”
Section: Factors Shaping the Development Of Vegetation In The Littoramentioning
confidence: 99%
“…The long-term occurrence of high water levels contributes to the transformation of zones towards the development of rush vegetation [10][11][12][13]. Then, the disappearance of vegetation characteristics of terrestrial and ecotone habitats can be observed.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of anthropogenic stressors and climate change on water-level and aquatic vegetation has been evident in recent decades [1][2][3] ENREF_1. The interaction between anthropogenic stressors, land-use change, and water-level variability affects aquatic macrophytes to a great extent [4][5][6][7]. Aquatic macrophytes are a diverse group of photosynthetic organisms that grow permanently or periodically in wetlands, the shoreline of lakes and along streams [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Distribution and composition of macrophyte communities are influenced by nutrient load, and climatic and hydrological conditions such as spatial and temporal variations of water level [7,11,[15][16][17][18]. Lake water level changes provide an opening for seedling recruitment for perennial emergent aquatic plants [19][20][21].…”
Section: Introductionmentioning
confidence: 99%